Analysis of POT Branding House Brand Personality Using Jennifer Aaker's Brand Personality Scale (Journal of Innovation, Business and Entrepreneurship, 2020)
The creative industry growth in Indonesia is promising, it has contributed 7.38% to the total national economy. Kemenparekraf states that the 8,14% development rate caused by the high demand from millennials for the business branding, visual identity system, advertising and others necessity. In practical terms, Indonesia Graphic Design Association showcases the data that the amount of practitioners in Indonesia holds the biggest amount compared to other ASEAN countries, either as a self-designer or design agency and studio. Humane, as one of the design studios in Bandung captures the problems that arise along with the visual communication design industry development. The research problem is specific at the tight competition in the design industry. Therefore, as Humane Studio starts growing, an initial strategy to create competitive advantage should be considered.The methodology of the research conducted with a quantitative approach and for the data collected by distributed online questionnaires through Instagram. The collected data then analyzed using SEM PLS with confirmatory factor analysis. The dependent variable is the Brand Personality and for the independent variable is the five brand personality dimensions. The result shows that, among five variables, the brand personality that represents POT Branding House is the Sincerity dimension.Keywords : brand personality, brand personality scale, competitive advantage, design studio, SEM PLS.